STRATEGI MASYARAKAT DALAM PENGELOLAAN LIMBAH RUMAH TANGGA (Studi di Desa Waylayap RT/RW 001 Kecamatan Gedongtataan Kabupaten Pesawaran Lampung) - Nesi Noviyanti; Ridhah Taqwa; Mery Yanti (Jurnal Media Sosiologi (JMS), 2021)
This study aims to analyze and understand the problems respecting how the community's strategy in managing household waste in Waylayap Village RT / RW 001, Gedongtataan, Pesawaran District, Lampung. The concept used in this research is the strategy from Irwan 2016. The research method used is descriptive qualitative, the data collected is qualitative and presented descriptively. The technique used in collecting the research data is using observation. Interviews and documentation. The data sources presented are primary data, namely the results of interviews with research informants and supplemented with secondary data regarding the community's strategy for managing household waste in Waylayap Village. The result of this discussion is that the management of household waste carried out by the community is caused by the absence of a landfill location which causes the community to take the initiative to carry out a strategy for managing household waste independently, the selection of this location is motivated by the existence of a river which is a place to dispose of household waste by several communities as well as the existence of waste management resulting from daily household activities carried out by the community.